Electrochemical Properties of Electrodeposited MnO2 Nanoparticles - Ali, Gomaa A. M.; M. M., Yusoff; K. F., Chong (Trans Tech Publications, Switzerland, 2015)
The present study shows the electrodeposition of MnO2 from KMnO solution and its electrochemical studies. XRD and FESEM analyses showed the electrodeposited MnO2 had nano-sized particle of 18 nm. The electrochemical properties had been investigated using the cyclic voltammetry, galvanostatic charge/discharge and impedance techniques in 1 M Na as electrolyte. The electrodeposited MnO showed good electrochemical behavior with high specific capacitance value of ca. 326 F g2-1. Moreover, it showed high capacitance stability of 84% over 1750 charge/discharge cycles as well as high columbic efficiency of 94 %. Impedance spectra showed low solution and charge transfer resistances, an indication of the conductive nature for the electrodeposited film.